Decoding Public Policy: How Cultural Dynamics Shape Decision-Making in Indonesia’s Political Landscape - Rochmansjah, Heru; Saputra, Romi (Journal of Ethnic and Cultural Studies, 2024)
This study explores how cultural dynamics shape public policy in Indonesia, focusing on the influence of cultural dimensions on policy-making processes and outcomes. The purpose is to understand the impacts of Indonesian cultural values on various policy sectors, including education, health, environment, and economic development. Employing a qualitative research approach, the study relies exclusively on secondary data from academic literature, government reports, and media sources to examine these cultural influences. Findings reveal that high power distance leads to centralized decision-making, while collectivism shapes policies toward community welfare. High uncertainty avoidance results in rigid regulatory frameworks, and traditional gender roles affect gender-related policies. Sector-specific analyses highlight the integration of traditional knowledge in environmental policies and the challenges of balancing modernization with cultural heritage in economic policies. The implications of these findings suggest that policymakers should incorporate cultural considerations into policy design to enhance effectiveness and inclusivity. This research contributes original insights into the intersection of culture and policy, emphasizing the need for culturally sensitive approaches in diverse governance contexts. By shedding light on how cultural factors impact policy formulation and implementation, the study offers valuable guidance for developing culturally relevant and effective policies addressing societal needs.